ANALYSIS OF THE ROLES OF TEAM WORK AND TEAM COMMUNICATIONS ON EMPLOYEE PERFORMANCE OF FUTURES TRADING BROKERAGE COMPANIES - Sutrisno, Sutrisno; Jaya, Fanlia Prima (Jurnal Ekonomi, 2023)
Study this explains the influence of cooperation team and communication team in the company with the impact on variables performance employee. Object in a study this namely PT. Mahadana Asta Futures. The aim of study this is to (1) for now and analysing the influence of communication teams and cooperation teams on the performance of employees. (2) for now and analyze the variable that has an influence dominant to the performance of employees. Obtained data in a study is primary data with the method spread questionnaire to respondents. The study uses the method quantitative through a questionnaire survey spread through google forms to the next 30 respondents processed with the use of SPSS version 20.0 with the method taking the sample is non-probability sampling. Results test hypothesis (t-test) that Teamwork has an effect significant on the performance of employees with t count as big (0.687) ≥ T table (2.048). Communication team influential significant to performance employee with t count of (5.851) ≥ T table (2,048) with coefficient determination by 94%. Teamwork and _ communication team are influential and significant in a manner simultaneous to the performance of employees. Implications from the study could give understanding to a researcher for notice and build cooperation team and communication team good.